Utilitarism, Equivalence Scales and Logarithmic Utility - Kjell Arne Brekke (Statistics Norway, Research Department, 1994)
It is shown that if social welfare is the sum of logaritmic utility function, the optimal income distribution and the welfare effect of any income redistribution is independet of the equivalence scales. In optimum all households have the same per capita income. Based on this observation it is discussed to what extent traditional welfare theory can be said to be concerned about fair income distribution.
Keywords: D10; D31; D63; 330; Equivalence scales; income distribution; logarthmic utility.